2007
DOI: 10.1016/j.limno.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Does groundwater influence the sediment fauna beneath a small, sandy stream?

Abstract: Gradients in the sediment fauna comprising groundwater (GW) and hyporheic taxa were investigated in the sand/ silt-bottomed Marbling Brook in Western Australia. The structure of sediment invertebrate assemblages from Marbling Brook sediments and the adjacent GW were studied at five sites over 1 year and hydrological interactions were characterized using a suite of abiotic factors. Although all five stream sites were upwelling, the sites differed in the degree of hydrological interactions between GW and surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…One study indicated a direct correlation between rate of groundwater discharge and abundance and taxonomic richness (Hunt et al, 2006), while another showed little correlation (Schmidt et al, 2007). Few studies have related groundwater discharge with mussel abundance and species richness.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated a direct correlation between rate of groundwater discharge and abundance and taxonomic richness (Hunt et al, 2006), while another showed little correlation (Schmidt et al, 2007). Few studies have related groundwater discharge with mussel abundance and species richness.…”
Section: Discussionmentioning
confidence: 99%
“…From upstream to downstream, the gauge stations include USGS 06797500 (near site C), 0679900 (about 27.5 km to upstream site F), 06799100 (about 17 km to downstream site G) and 06799350 (near site H). According to the stream flow data (http://waterdata.usgs.gov/nwis), during our investigation, the average stream flows from the four gauging stations were 0.89, 15 The number and dates of the tests are summarized in Table 1.…”
Section: Study Area Descriptionmentioning
confidence: 96%
“…However, evidence shows that hyporheic exchange connects surface water and groundwater in rivers [5][6][7][8][9]. Therefore, the clogged layer may be destroyed with spatial and temporal variations.…”
Section: Introductionmentioning
confidence: 99%